"Degradabilidad y cinética ruminal in situ de las cáscara de tres variedades de maracuyá (Passiflora edulis)". - Bone Flores, Denisse Stefanía (2020)
This research was carried out in the experimental farm '' La Maria '' Laboratory of Rumiology and nutritional metabolism (RUMEN), Quevedo State Technical University located at km 7 ½ via Quevedo - El Empalme, Los Ríos Province, at 01 ° 06 '30' 'west latitude and at a height of 73msnm. Its objective was to determine the degradability and ruminal kinetics in situ of the peel of three varieties of passion fruit (passiflora edulis), yellow, red and improved (yellow x red). A completely randomized block design (DBCA) was applied with 4 repetitions where each experimental unit was made up of a fistulated bull in the rumen and three treatments T1 CMA (Yellow passion fruit peel), T2 CMR (Red passion fruit peel) and T3 CMA x CMR (yellow passion fruit shell x red) and seven incubation times (0,3,6,12,24,48 and 72 hours) and for the differences between the Tukey averages (P≤0,05). The in situ degradation of the dry matter of the three varieties of passion fruit peel determined a better percentage of degradability at 48 hours of incubation in the red passion fruit peel T2 with (66,37) followed by T3 and T1, the rate of passage (k0.02) in T2 (CMR) was higher (46.03) than the other treatments and with a speed rate of 5%. Keywords: Passion fruit, ruminants, food, degradability, kinetics.